Deciphering the role of phosphorus management under conservation agriculture based wheat production system - Kumar, Amit; Behera, Uma Kant; Dhar, Shiva; Babu, Subhash; Singh, Raghavendra; Upadhyay, Pravin Kumar; Saha, Saurav; Devadas, Ramgopal; Kumar, Adarsh; Gupta, Gaurendra; Singh, Ramesh Kumar; Gudade, Bharat Arjun; et al. (Frontiers in Sustainable Food Systems, 2023)
Phosphorus (P) is a vital element required by all living organism (plants, animals and microbes etc.). Its application in agriculture, whether in conventional or conservation agriculture, requires careful attention due to its low use efficiency, which typically does not exceed 20%. With the increasing acceptance of conservation agriculture (CA), it is crucial to develop protocols for P management to ensure sustainable wheat production. Therefore, a field trial was conducted from 2016–2017 to 2017–2018 in the India's semiarid eco-region to study the role of P on wheat productivity, quality, and resource use efficiency under CA-based production system. We assessed the impact of tillage operations and P management practices on wheat productivity, quality, and resource use efficiency. Three tillage and residue management options such as CT-R (conventional tillage without residue); NT-R (no tillage without maize residue) and NT + R (no tillage with maize residue @ 2.5 Mg ha−1) were laid-out in main plot and five P management options subplots viz. P1 (nitrogen and potash according to recommended but not P); P2 (17.2 kg P ha−1); P3 (17.2 kg of P ha−1 + microbial fertilizer); P4 (17.2 kg P ha−1 + compost inoculant culture) and P5 (34.4 kg P ha−1) in split plot design with three replicates. The results indicates that the combination of no-tillage with residue retention (maize residue @ 2.5 Mg ha−1) (NT + R) and the application of 34.4 kg P ha−1 (P5) significantly improved grain yield by ~43.2% compared to the control treatment (conventional tillage with no residue, CT – R, and no phosphorus application). NT + R also resulted in significantly better amino acid (~22.7%) and net protein yield (~21.2%) compared to CT – R. Regarding the P management strategy, the highest amino acid (49.1%) and protein yield (12.5%) were observed under the P5 treatment compared to the no-phosphorus treatment. Conjoint use of NT – R, along with the application of 17.2 kg P ha−1 and PSB (Phosphorus Solubilizing Bacteria), resulted in a significant increase in energy use efficiency of ~58% over other treatments combination. Furthermore, the NT + R plot that received 17.2 kg P ha−1 + PSB demonstrated higher P agronomic efficiency (~43%) and recovery efficiency (~53%) over control. The study's findings underscore the significance of adopting efficient P management strategies in CA to ensure the sustainable production of wheat.